PENGELOLAAN ASPIRASI MASYARAKAT DAN PENGAWASAN PENGELOLAAN KEUANGAN DESA DI DESA BEJI KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Since the management of village finances is so complicated and difficult, the village secretary and village treasurer need assistance so that the preparation of the APBDes is appropriate, transparent and accountable. Village financial management is the whole activity that includes: Planning, Implementation, Administration, Reporting, Accountability. Observing the description of managing community aspirations and supervising the management of village finances which is very important, the instructor team from FISIP Unwiku would like to hold community service in enlightening, coaching and mentoring the Beji Village BPD and all village officials so that the BPD is more optimal in absorbing, accommodating and channeling aspirations public. The method used in this service is counseling and mentoring which is delivered directly by the Assistance Team. The results of the service program show that the community delivers good appreciation and after participating in this community service activity, the Beji Village Government and its community understand the importance of managing community aspirations and overseeing village financial management in Beji Village, Kedungbanteng District, Banyumas Regency.